Analisis Manajemen Aset Sekolah Dasar 001 Kecamatan Karimun Kabupaten Karimun Dalam Mendukung Proses Pembelajaran - Clara, Brigita; Umiyati M.Si, Dr.Sri (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
This study aims to describe and analyze the asset management of facilities andinfrastructure in Karimun001 Primary School in supporting the learning process. This type ofresearch uses a qualitative approach.The research data were obtained through observation, interview, and documentation methods. Theinformants of this research are the coordinating teacher of facilities and infrastructure, administration,school committee and head of the fieldof primary school development of the Karimun district educationoffice. The object of this research is the analysis of asset management of facilities and infrastructure whichincludes planning, procurement, inventory, maintenance, and removal. The results of the research on assetmanagement of facilities and infrastructure in primary school 001 karimun sub-district, namely: 1)Planning is carried out once a year and a joint meeting is held first but there are obstacles to the sourceof funds.2) Procurement is carried out according to the needs that have been planned.3) Investarization isalready runningbut there are obstacles to asset coding.4) Maintenance is carried out together withteachers, students and school committees 5) Deletion is carried out by recording goods then submittingarequest letter to the Education Office.